2023
DOI: 10.3390/ma17010073
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress in Special Engineering Plastic-Based Electrochromic Polymers

Yixuan Liu,
Zhen Xing,
Songrui Jia
et al.

Abstract: SPECPs are electrochromic polymers that contain special engineering plastic structural characteristic groups (SPECPs). Due to their high thermal stability, mechanical properties, and weather resistance, they are also known as high-performance electrochromic polymer (HPEP or HPP). Meanwhile, due to the structural characteristics of their long polymer chains, these materials have natural advantages in the application of flexible electrochromic devices. According to the structure of special engineering plastic gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 128 publications
(224 reference statements)
0
4
0
Order By: Relevance
“…Each battery had a long lifetime and a low average capacity degradation rate, as was predicted. The D−π–A conjugated structures of PTTB organic electrodes are less soluble in aqueous electrolyte, which contributes to the increased cycling stabilities of the batteries. , Furthermore, the 99% Coulombic efficiencies show the strong redox reversibility during cycling. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each battery had a long lifetime and a low average capacity degradation rate, as was predicted. The D−π–A conjugated structures of PTTB organic electrodes are less soluble in aqueous electrolyte, which contributes to the increased cycling stabilities of the batteries. , Furthermore, the 99% Coulombic efficiencies show the strong redox reversibility during cycling. , …”
Section: Resultsmentioning
confidence: 99%
“…69,70 Furthermore, the 99% Coulombic efficiencies show the strong redox reversibility during cycling. 71,72…”
Section: Solvatochromic Effectmentioning
confidence: 99%
“…We also investigated the phenomenon of electrochromism, which involves reversible colour changes produced by the injection and extraction of charges into and out of an active material during electrochemical redox processes, to better understand the dual functions of a single substance. 24,25 TPA, a typical EC material, has a propeller-shaped structure that flattens and changes to give a more highly conjugated conformation when the lone pair of electrons on nitrogen is removed, resulting in distinct absorption peaks in the visible spectrum. 26–29 Moreover, TPA contains many polymerizable active sites, is easily modified, and is frequently utilized to construct EC polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochromic materials have attracted great attention due to their reversible optical change properties [ 1 , 2 ]. It has been demonstrated that organic conjugated polymers and viologens used as electrochromic materials have more advantages than inorganic compounds, including high CE, fast switching speed, easy of large-area processing, and easy color tuning through chemical modification [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Therefore, they have promising applications in various fields, such as smart windows, memory devices, rear view mirrors, and information displays.…”
Section: Introductionmentioning
confidence: 99%